2021
DOI: 10.1182/blood-2021-152068
|View full text |Cite
|
Sign up to set email alerts
|

Opportunistic Infections in Patients Receiving Daratumumab Regimens for Multiple Myeloma (MM)

Abstract: Background Daratumumab-based treatment regimens for MM have improved outcomes for both transplant-eligible and ineligible patients. As a result, patients are receiving longer exposure to this CD38 targeting monoclonal antibody. Adverse events (AE) including hypogammaglobulinemia, neutropenia, and lymphopenia have been reported in both clinical trials and retrospective studies, but with limited and contrasting data on the associated risk of developing infections. Furthermore, there remains a pauc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
2
2
0
Order By: Relevance
“…42 disseminated cryptococcosis are reported. [43][44][45][46][47][48][49][50] As expected, infections occur at a higher rate in those patients with higher grade neutropenia and lymphopenia, notably heavily pretreated patients treated with combination regimens within the initial 6 months of treatment. In this population treated with daratumumab, the median time to severe infection was ~50 days in patients with severe lymphopenia versus ~90 days in those without severe lymphopenia.…”
Section: Fda-approved Next-generation Therapeuticssupporting
confidence: 57%
See 1 more Smart Citation
“…42 disseminated cryptococcosis are reported. [43][44][45][46][47][48][49][50] As expected, infections occur at a higher rate in those patients with higher grade neutropenia and lymphopenia, notably heavily pretreated patients treated with combination regimens within the initial 6 months of treatment. In this population treated with daratumumab, the median time to severe infection was ~50 days in patients with severe lymphopenia versus ~90 days in those without severe lymphopenia.…”
Section: Fda-approved Next-generation Therapeuticssupporting
confidence: 57%
“… 42 Atypical infections are uncommon, however, reactivation of herpes zoster and Epstein–Barr virus/cytomegalovirus, pneumocystis jirovecii pneumonia (PJP), progressive multifocal leukoencephalopathy, bronchopulmonary aspergillosis, fungal meningitis, listeriosis, and disseminated cryptococcosis are reported. 43 50 As expected, infections occur at a higher rate in those patients with higher grade neutropenia and lymphopenia, notably heavily pretreated patients treated with combination regimens within the initial 6 months of treatment. In this population treated with daratumumab, the median time to severe infection was ~50 days in patients with severe lymphopenia versus ~90 days in those without severe lymphopenia.…”
Section: Fda-approved Next-generation Therapeuticssupporting
confidence: 57%
“…Unfortunately, from an extended clinical review of the pivotal randomized phase 3 clinical trials examining the current use of anti-CD38 mAbs in MM, the addition of anti-CD38 mAbs resulted in a higher rate of AEs in the overall population, particularly in terms of infections (including pneumonia) and neutropenia plus lymphocytopenia. In fact, as regards infectious diseases, the FAERS suggests a significant association between daratumumab-based regimens and multiple opportunistic infections [4] and pivotal randomized phase 3 clinical trials documented that the rates of infectious complications, in particular respiratory tract infections including viral complications, are higher in the anti-CD38 mAbs combination with IMiDs or PIs plus dexamethasone group than IMiDs or PIs and dexamethasone alone. In the same line, a recent metanalysis of clinical trials [39], pooling five randomized phase 3 studies (ALCYONE, MAIA, CASSIOPEIA, CASTOR and POLLUX), confirmed that the incidence of TD due to infection/pneumonia was slightly higher with daratumumab than in the control group (0.95% vs 0.73%); conversely, the rates of TD due to treatment-emergent adverse events (TEAEs) (6.77% vs 10.08%) and treatment-related deaths (3.61% vs 4.34%) were significantly lower in the daratumumab group than in the control arm.…”
Section: Discussionmentioning
confidence: 99%
“…The anti-CD38 monoclonal antibodies (mAbs)-based therapies are approved for NDMM and RRMM and their use has changed the frequency and epidemiology of infections. The Food and Drug Administration's Adverse Events Reporting System (FAERS), a pharmacovigilance monitoring database, recently reported the characteristics and incidence of infections in patients with MM treated by daratumumab [4]. The FAERS showed that 2.7% of 7152 adverse events (AEs), in the period 2015-2021, were opportunistic infections from Herpes Zoster (25.1%), CMV (22.0%) and Hepatitis B Virus reactivation (6.7%), Pneumocystis Jirovecii Pneumonia (17.4%), bronchopulmonary Aspergillosis (8.2%) and tuberculosis (2.5%) [4,5].…”
Section: Introductionmentioning
confidence: 99%